Production and Evaluation of Immunity Boosting Instant Soup Mix From Moringa Oleifera Lam.pod Powder (Bangladesh Journal of Botany, 2022)
Standardizationof best combination for the development of immunity boostinginstant soup mix, various quality parameters, the storage stability and cost estimation of product were evaluated. Protein in instant soup ranged from 9.76 to 11.89 percent in different formulations of instant soup mix. Formulation MPP4 (11.89) had significantly maximum protein content followed by MPP3, MPP2, MPP1 and control with the minimum protein content. The original immunity boostinginstant soup mix (control) exhibited highest carbohydrate content (61.52%) followed by MPP1, MPP3, MPP4, and MPP2 with lowest content. The evaluated scores of control for colour and appearance, taste, flavour, consistency, after taste and overall acceptability were 8.36, 8.50, 8.60, 8.90, 8.76 and 8.63, respectively.Bangladesh J. Bot. 51(1): 75-81, 2022 (March)